FBXO38 Drives PD-1 to Destruction. Issue 2 (February 2019) - Serman, Taryn M.; Gack, Michaela U.
Abstract : Aberrant expression of T cell-resident programmed cell death protein-1 (PD-1) is known to promote tumor progression. A recent study ( Nature 2018;564:130–135) has now identified the E3 ubiquitin ligase FBXO38 as a crucial regulator of PD-1 protein turnover in T cells, providing a novel mechanism for potential use in cancer immunotherapy.